Associations between school climate and student life satisfaction: resilience and bullying as mediating factors - Aldridge, Jill; McChesney, K.; Afari, Ernest (2020)
Because adolescent life satisfaction is associated with important affective, behavioural and health-related outcomes during both adolescence and later life, strategies for promoting adolescent life satisfaction have potential social value. In the study reported in this article, associations are reported between perceptions of the school climate and reports of bullying, resilience and life satisfaction for 6120 Australian adolescents. The study extended past research, which has given little attention to either the relationships between these variables or the relative roles of various school climate sub-constructs. Aspects of the school climate explained 41% of the variance in adolescents’ resilience, 16% of the variance in bully victimisation, and 54% of the variance in life satisfaction. Further, resilience was positively associated with life satisfaction. These results affirm the importance of the psychosocial school climate as a mechanism for improving adolescent (and life-course) outcomes, strengthening calls for schools to give greater attention to improving their psychosocial climates.